THE EFFECT OF PERSONAL AND GENERAL UNEMPLOYMENT ON SUBJECTIVE WELL-BEING - Novak, Matic (European Scientific Journal, ESJ, 2014)
This paper aims to add a multilevel perspective to understanding of self-reported wellbeing. Not only individual level factors but also country level determinants influence our satisfaction, therefore single level models that prevail in the analysis of subjective well-being are not appropriate. The main focus lies in the analysis of the impact of personal unemployment and country‘s unemployment rate on life satisfaction of individuals. A twolevel regression model is developed. Factors describing individual’s characteristics are included at the within level, while gross national income per capita and unemployment rate are between level variables. In order to obtain the moderating effects of unemployment rate on the influence of individual’s employment status on subjective well-being, a random intercept random slope model is estimated using the cross-sectional data from the sixth wave of World Values Survey. The results show that the negative effect of personal unemployment increases with the unemployment rate in the economy.